1998
DOI: 10.1007/s003359900816
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of 82 expressed sequence tags from a cattle ovary cDNA library

Abstract: In total, 82 ESTs were generated from 51 unique clones randomly selected from a cattle ovary cDNA library. Among these clones, 22 (42.1%) had 5' and/or 3' ends that matched with known human or other mammalian coding sequences, 18 (35.3%) matched human or other ESTs, and 11 (21.6%) represented novel transcripts with no significant match to any sequence in the databases. The relatively high frequency of ESTs with no matches in GenBank or dbEST indicates that bovine ovary may be a source of novel candidate genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
4

Year Published

1998
1998
2004
2004

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 20 publications
0
33
0
4
Order By: Relevance
“…The COMPASS strategy (Ma et al 1998;Rebeiz and Lewin 2000;Larkin et al 2003) was used to target more than 900 new Comparative length of chromosome is the total length minus area of telomere, centromere, and heterochromatin regions. The full length of the chromosome is given in parentheses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The COMPASS strategy (Ma et al 1998;Rebeiz and Lewin 2000;Larkin et al 2003) was used to target more than 900 new Comparative length of chromosome is the total length minus area of telomere, centromere, and heterochromatin regions. The full length of the chromosome is given in parentheses.…”
Section: Discussionmentioning
confidence: 99%
“…Markers were selected for mapping using the COMPASS strategy (Ma et al 1998;Band et al 2000;Rebeiz and Lewin 2000;Larkin et al 2003). All of the 47,787 cattle ESTs in the April 2000 GenBank release were used as a resource for filling gaps in the firstgeneration comparative map (Band et al 2000).…”
Section: Methods Marker Selection and Mapping Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Expressed sequence tag (EST) analysis of gene expression in specific tissues is widely used to characterise gene function and tissue physiology [13]. This approach has been used to accelerate gene discovery in a variety of bovine tissues including the ovary [14], mammary gland [15], embryo [16], foetus [17], and multiple tissues [18]. In addition, a recent study reported the identification and mapping of 11 gene sequences preferentially expressed in the bovine CL [19].…”
Section: Introductionmentioning
confidence: 99%
“…A new strategy of comparative mapping by annotation and sequence similarity (COMPASS; ref. 18) has accelerated the comparative gene-mapping process (19,20). By using this approach, more than 1,000 markers were assigned and presented in a combined first generation cattle WGRH 5,000 and cattle͞human whole-genome comparative map (21).…”
mentioning
confidence: 99%